ACCUMULATION OF METAL(OIDS) IN MYOCARDIAL TISSUE AND THE MECHANISMS UNDERLYING THEIR CARDIOTOXIC EFFECTS: N/A - Cirovic, Ana; Tasic, Nebojsa (Medicinski podmladak, 2023)
Heavy metals could exert a strong cardiotoxic effect, since cardiomyocytes are in general vulnerable cells, very sensitive to heavy metals-induced toxicity. The correlation between exposure to heavy metals and their contribution to the pathophysiology of diverse cardiovascular disorders, such as coronary artery disease (CAD) and cardiomyopathies (CMPs), has gained recognition primarily through clinical investigations wherein metal(oids) levels were quantified in the blood or urine of individuals afflicted with said disorders. However, a crucial perspective is absent due to the absence of studies that investigate the accumulation of heavy metals within cardiac tissue. These studies, whether post-mortem or involving heart samples obtained during invasive procedures, are currently lacking. To achieve a comprehensive understanding of the potential involvement of metal(oids) in the genesis of e.g. CMPs or CAD, these inquiries are indispensable. Furthermore, certain comorbidities like iron deficiency may expedite the bioaccumulation of myocardial heavy metals by augmenting the density of transferrin receptor 1 (TfR1). The impact of heavy metals on the heart’s contractile machinery, coupled with their potential to initiate mitochondrial apoptosis through triggered pathways, forms part of the intricate pathophysiological landscape. Central to these mechanisms is the generation of reactive oxygen species (ROS) and the peroxidation of macromolecules. This review shines a light on research findings pertaining to the bioaccumulation of heavy metals within the myocardium and elucidates the molecular mechanisms through which metal(oid)s induce cardiotoxicity